Closets and institutions: Queer teacher exclusion in the Israeli high school system. (September 2019) - Amoor, Izat El
Drawing on an analysis of 12 in-person qualitative interviews with queer, male, Israeli high school teachers, and Israeli queer social and political news stories, this study explores the intersection of queer teachers' professional and personal sexual identities. The study contends that this intersection is one characterized by exclusion, particularly attributable to institutional homophobia and queer politics situated within the Israeli national regional ground. Utilizing queer and educational discourses regarding teacher identity and institutional homophobia, this article documents and reports on queer teachers' resistance in the educational system and the navigation of the coming-out process in socio-politically complex Israel.